Anti-dengue virus antibodies that elicit complement-mediated lysis of Zika virion correlate with protection from severe dengue disease - Antonio G. Dias, Jr.; Elias M. Duarte; Jose Victor Zambrana; Jaime A. Cardona-Ospina; Sandra Bos; Vicky Roy; Julia Huffaker; Guillermina Kuan; Angel Balmaseda; Galit Alter; Eva Harris (Cell Reports)
Summary: Antibodies from primary dengue (DENV1–4) or Zika (ZIKV) virus infections can influence subsequent heterotypic infections, but their protective characteristics are not well defined. We analyzed pre-infection plasma samples from children in our Nicaraguan cohort study who later developed either dengue fever (DF; n = 31) or dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS; n = 33) upon secondary heterotypic DENV infection. Various antibody properties, notably antibody-dependent complement deposition, correlated with protection against DHF/DSS. Interestingly, this association was strongest when using recombinant ZIKV antigens despite participants being ZIKV naive. Additionally, complement-mediated virion lysis (virolysis) with ZIKV virions was strongly associated with protection, a finding replicated in an independent sample set. ZIKV virolysis emerged as the only antibody property linked to reduced risk of DHF/DSS and severe symptoms such as thrombocytopenia and plasma leakage. These results suggest that ZIKV-cross-reactive anti-DENV antibodies that mediate complement-dependent virolysis may lower the risk of severe disease, informing the development of effective dengue vaccines and therapeutics.